1943
DOI: 10.1136/hrt.5.3.152
|View full text |Cite
|
Sign up to set email alerts
|

Casual and Basal Blood Pressures I. In British and Egyptian Men

Abstract: In the course of clinical investigations on healthy Egyptian men, we observed that during a period of rest in the sitting posture the systolic blood pressure often fell below 90 and usually below 100 mm. of mercury. This led to a study of the blood pressures of British subjects resident in Egypt and of others resident in London. The pressure found under the conditions described below is called basal* blood pressure because it was not found possible to reduce it appreciably below this level by rest or sleep. Ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

1945
1945
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(8 citation statements)
references
References 2 publications
1
7
0
Order By: Relevance
“…They defined the casual pressure as the initial pressure taken without any rest, and the basal pressure was the minimum value obtained after a prolonged period of rest. Smirk's idea was that the basal pressure was the better predictor of cardiovascular risk (2). The difference between the casual and basal pressure was termed the supplemental pressure, and was roughly equivalent to what we now refer to as the white coat effect (WCE), as described below.…”
Section: Introductionmentioning
confidence: 99%
“…They defined the casual pressure as the initial pressure taken without any rest, and the basal pressure was the minimum value obtained after a prolonged period of rest. Smirk's idea was that the basal pressure was the better predictor of cardiovascular risk (2). The difference between the casual and basal pressure was termed the supplemental pressure, and was roughly equivalent to what we now refer to as the white coat effect (WCE), as described below.…”
Section: Introductionmentioning
confidence: 99%
“…Except in the group of subjects in which an hypnotic drug was given the method of basal blood pressure determination which was used throughout this study was that outlined by Smirk (1945), namely a combination of the routine described by the combined committee on blood pressure measurement and that of Alam and Smirk (1943). The procedure was designed to measure the blood pressure when the subject was in the--basal metabolic state and was free from states of emotion or mental alertness.…”
Section: Methodsmentioning
confidence: 99%
“…It should be determined 10 to 12 hours after the last meal of the previous night and after resting for half an hour in a warmed room." Alam and Smirk (1938) indicated that they were using a basal blood pressure as a base-line in studies of blood pressure raising reflexes and later (1943) obtained results approximating to the basal blood pressure with a procedure which they termed emotional desensitization to the presence of the observer and to the process, of sphygmomanometry, with special attention to rest in a warm quiet room, but taking no special precautions as to the time of day or the time after the last meal. Alam and Smirk, from observations of blood pressure obtained by this method, suggested that readings obtained under ordinary clinical conditions should be called casual blood pressures, and those obtained under basal conditions, basal blood pressures; and that the difference between casual and basal blood pressure levels should be called the supplemental blood pressure.…”
mentioning
confidence: 99%
“…This led to a study (Alam & Smirk, 1943;Smirk, 1944;Kilpatrick, 1948) of casual, basal and supplemental pressures. We introduced the term 'casual blood pressure' for the blood pressure as ordinarily measured.…”
Section: Introductionmentioning
confidence: 99%